Social Media and Crisis Communication: A Narrative Literature Review of Public Engagement and Policy Implications - Elfattah, Hagar Yehia Abd (Yayasan Sinergi Kawula Muda, 2024)
Social media has become a vital component in crisis communication, particularly during global emergencies such as the COVID-19 pandemic. This narrative review investigates how social media platforms are utilized by formal and informal actors to disseminate crisis-related information, shape public perception, and influence behavioral responses. Using a systematic literature review approach, scholarly articles were sourced from databases including Scopus, PubMed, Google Scholar, and Web of Science, focusing on studies from 2010 to 2024 that explore digital crisis communication in public health, natural disasters, and political crises. The review finds that governmental and health institutions use social media to broadcast real-time updates and counter misinformation. Informal communicators, such as influencers and citizen journalists, play a significant role in extending message reach, though not without challenges related to accuracy. Factors like digital literacy and public trust in institutions emerge as key determinants of communication effectiveness. Strategies such as clear messaging, visual aids, real-time engagement, and culturally contextualized content were identified as successful practices. This review highlights the critical need for education-driven interventions and collaborative communication frameworks that enhance public understanding and institutional legitimacy. It concludes that adaptive, data-driven strategies tailored to audience behavior and systemic contexts are essential for effective crisis communication in the digital age.